DETERMINAN KETAHANAN HIDUP LIMA TAHUN PENDERITA KANKER KOLOREKTAL DI RUMAH SAKIT KANKER DHARMAIS JAKARTA - Sitorus, Nikson (Publikasi Penelitian Terapan dan Kebijakan, 2010)
Colorectal cancer (CRC) disease is a kind of cancer disease with increasing incidence,prevalence and mortality nowadays. This research was aimed to know the determinant of five yearsurvival of colorectal cancer patients. The research design was retrospective cohort. The sampleswere 79 colorectal cancer patients who got their first treatment in RSKD from 1998 to 2004.Bivariate analyzed by using log rank test and cox regression. The result was found that the numberof colorectal cancer patients death during 5 years of follow up were 34 patients (43,1%). The overall patients probability of 5 years survival was 31,43% with 30 months median. The probability of 5years survival according to Dukes B was 52,38%, Dukes C was 34,64% and Dukes D was 12,7%.The earlier stadium was 52,38% and the advance stadium was 25,71%. The bivariate analysisfound that the clinical stadium, the tumor location and treatment utility were related to the 5 yearssurvival of the patients while the histopatology, cell differentiation degree, age, sex, bleedingsymptoms and marital status were statistically not related.